The relationship between reserves and accruals – with reference to the issue of earnings management in public companies - Comporek, Michał (Związki gospodarowania rezerwami z memoriałowymi korektami zysku netto – odniesienie do problematyki zarządzania wynikiem finansowym w spółkach giełdowych, 2018)
The main objective of the study is to examine the relationship between the implemented reserves policy and the value of accruals reported in the financial statements of public companies listed on the Warsaw Stock Exchange. Both research fields are considered as the main areas of earnings management, which can be seen both as the pursuance of a true and fair view of the economic situation of a business entity and as the intentional manipulation of the results of an economic activity in order to mislead selected stakeholders of company. Empirical studies were conducted among public companies included in the WIG20, mWIG40 and sWIG80 stock indices, whose shares have been traded on the stock market for at least 10 years in the assumed horizon of 1997-2016
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 3, s. 17-33
Keywords: reserves; provisions; earnings management; accruals; net income; rezerwy; korekty zysku netto; zarządzanie zyskiem; wynik finansowy